Biodiesel dari Limbah Pabrik Gula dan Minyak Jarak Pagar (Jatropha curcas) dengan Katalisator Zeolit Alam Klinoptilolite - Harjanti, Ratna Sri; Rahmanta, Anugrah Perdana (Universitas Ahmad Dahlan, 2015)
The fuel price increase with the increase of the number of transportation due to the increasing numbers of the population. Indonesia with more than 200 million people in need of transportation fuels in the form of gasoline and diesel in large quantities. Currently the main source of transportation fuels derived from petroleum. Premium production in Indonesia is about 62 million barrels and production of about 87 million barrels of diesel fuel. The product does not include the use for other needs, such as lubricating oil, kerosene, avgas, as well as other materials. This is particularly worrying given the oil reserves are dwindling. One of the alternative energy for transportation fuels is biodiesel as a substitute for diesel fuel.The castor oil has potential to be used as biodiesel. Fusel oil is a sugar mill waste containing alcohol. The reaction between castor oil and fusel oil with natural zeolite catalyst klinoptilolite be referred to as alcoholysis reactions that produce esters. Castor oil and fusel oil mixed with zeolite powder klinoptilolite that previously had been heated in a separate place until it reached its boiling temperature. Three neck flask fitted with a thermometer, hoses trailer makers, heater, and the agitator on 100 rpm with 100 oC of temperature. Snapshot taken at intervals of 30 minutes each. Conversion reaction calculated by analyzing the levels of glycerol bottom layer by means asetin. Alcoholysis fusel oil and castor oil with natural zeolite catalyst klinoptilolite produce esters that are approaching the properties of diesel oil with a calorific value of 19 119 Btu/lb. Optimum conversion of 57 % was obtained in alcohol - oil ratio of 9.29 mgek/mgek and the addition of a catalyst as much as 2.56% of the weight of oil.